2016
DOI: 10.3390/nu8110668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Walnut Consumption on Mood in Young Adults—A Randomized Controlled Trial

Abstract: Walnuts contain a number of potentially neuroprotective compounds like vitamin E, folate, melatonin, several antioxidative polyphenols and significant amounts of ω-3 fatty acids. The present study sought to determine the effect of walnuts on mood in healthy volunteers. Sixty-four college students were randomly assigned to two treatment sequences in a crossover fashion: walnut–placebo or placebo–walnut. At baseline mood was assessed using Profiles of Mood States (POMS). Data was collected again after eight week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…In the PREDIMED trial, an RCT with the Mediterranean diet supplemented with nuts showed a 40% lower risk of depression in patients with T2DM (RR = 0.59, 95% CI 0.36–0.98) [ 18 ]. An RCT conducted by Pribis et al [ 19 ] explored the effect of walnut consumption on mood in young adults and observed a significant medium effect size improvement in the Total Mood Disturbance Score (−27.5%, p = 0.043) in males. Another reason for the inconsistent results with other studies may be the different participants in their studies who were obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PREDIMED trial, an RCT with the Mediterranean diet supplemented with nuts showed a 40% lower risk of depression in patients with T2DM (RR = 0.59, 95% CI 0.36–0.98) [ 18 ]. An RCT conducted by Pribis et al [ 19 ] explored the effect of walnut consumption on mood in young adults and observed a significant medium effect size improvement in the Total Mood Disturbance Score (−27.5%, p = 0.043) in males. Another reason for the inconsistent results with other studies may be the different participants in their studies who were obese.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the synergy and interaction of all the nutrients and other bioactive components in nuts have a beneficial effect on brain, cognition, and neuropsychiatric disorders [ 16 , 17 ]. Various interventions [ 18 , 19 ], along with two recently published cohort studies [ 20 , 21 ], have found higher nut consumption was associated with lower depression scores. A cohort study in Tianjin, China indicated that nut consumption may be beneficial in the prevention of depressive symptoms [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of change in measures of mood differs from findings in previous studies. Short term walnut consumption has been shown to improve mood in non-depressed healthy young men [30] and a short term cross-over intervention with a Mediterranean style diet containing nuts also reported improvements in alertness and contentment compared with habitual diet [59]. It has been suggested that improvements in mood may be associated with a higher consumption of magnesium [60] and whilst the AED resulted in a significant increase in magnesium intake this did not result in significant changes in alertness.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown improvements in short-term memory, verbal fluency, and processing speed when middle-aged to older healthy adults consumed Hi-Oleic peanuts (56-84 g/day) for 12 weeks. There has been one pilot study with Brazil nuts in older adults with mild cognitive impairment showing an improvement in verbal fluency and constructional praxis after 6 months of supplementation with one Brazil nut per day [27].Cross-sectional analyses of cohort studies have observed lower depression scores in habitual nut consumers [28,29], and one study showed that 8 weeks of walnut consumption in young healthy non-depressed adult males improved total mood disturbance [30]. It has been proposed that the nutrient profile of nuts may be neuroprotective, and a small number of intervention studies have compared the effects of consuming nuts on mood.Co-monitoring cardiometabolic measures with mood and cognition may provide insight into the mechanisms underlying any changes in neurocognitive performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation